1983
DOI: 10.1107/s0021889883009929
|View full text |Cite
|
Sign up to set email alerts
|

Information retrieval from X-ray small-angle scattering with polychromatic (`white') synchrotron radiation

Abstract: The possibilities of obtaining structural information from X-ray small-angle scattering experiments with 'white' polychromatic synchrotron radiation using line collimation are investigated by numerical simulation. Theoretical scattering curves of geometrical models were smeared with the appropriate wavelength distributions and slit-length functions, afflicted by statistical noise, and then evaluated by identical methods as normally used for experimental data, as described previously [program ITP;Glatter (1977)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…The increased¯ux would then more effectively allow time-resolved experiments with smaller amounts of often dif®cult-to-obtain biological samples. It is also very important to obtain solution scattering data at higher Q values with good statistics, primarily for three reasons: (i) some proteins (mostly oligomeric) exhibit subsidiary scattering peaks that are sensitive to the changes in subunit arrangements, which are often linked to biological functions; (ii) higher-angle data are needed to make accurate indirect Fourier transforms to obtain additional structural information such as distance distribution functions of a protein; and (iii) the Kratky plot at relatively high angles is often used to distinguish folded protein structures from unfolded ones (Kataoka et al, 1993). Solution scattering intensity falls very quickly with angle, resulting in very weak signal levels being observed at higher angles.…”
Section: Cholesterol Myristate Powder Diffractionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased¯ux would then more effectively allow time-resolved experiments with smaller amounts of often dif®cult-to-obtain biological samples. It is also very important to obtain solution scattering data at higher Q values with good statistics, primarily for three reasons: (i) some proteins (mostly oligomeric) exhibit subsidiary scattering peaks that are sensitive to the changes in subunit arrangements, which are often linked to biological functions; (ii) higher-angle data are needed to make accurate indirect Fourier transforms to obtain additional structural information such as distance distribution functions of a protein; and (iii) the Kratky plot at relatively high angles is often used to distinguish folded protein structures from unfolded ones (Kataoka et al, 1993). Solution scattering intensity falls very quickly with angle, resulting in very weak signal levels being observed at higher angles.…”
Section: Cholesterol Myristate Powder Diffractionmentioning
confidence: 99%
“…The latter is true for small-angle scattering studies on noncrystalline biological systems; here, one would like to increase the monochromator bandpass to a few percent or more (as is common in neutron scattering) in order to obtain a signi®cant gain in beam¯ux. Glatter & Laggner (1983) demonstrated that one could still retrieve a reasonable amount of structural information from small-angle scattering patterns using a polychromatic (i.e. white) synchrotron radiation beam.…”
Section: Introductionmentioning
confidence: 99%